The Objectives of the Finance Function - Jaramillo Moscoso, Eduardo (2010)
The goal of financial management is to maximize the company's stock value. But the purpose of good financial management should be focused on actions that not only maximize this value, but should also be able to resolve questions such as: what assets should the company acquire? What volume of assets should you have? How should you finance your capital needs? The role of a financial director, under the gaze of modern finance, is no longer focused solely on obtaining resources, but also seeks profitable investment projects and contributes with the appropriate analytical instruments that allow you to respond to problems. that today's companies present.